Kirigami the art of cutting & folding paper - An, Ho Huu; Arnac, Laurence (Tunbridge Wells, Kent Search Press, 2013)
Projects include pop-up greeting cards, Christmas decorations, and more, combining traditional Japanese motifs such as snowflakes, orchid blossoms and pentagrams with modern designs to provide ideas and inspiration for contemporary paper crafters
Arts (Papercrafts)
Translated from the French
1 2 13 14
Keywords: Paper work